Case Report: Primary catastrophic antiphospholipid syndrome in a pediatric patient with cerebral venous sinus thrombosis as the first manifestation - Xu, Lingyang; Wu, Jing; Wang, Haidong; Yang, Baowang (Frontiers in Pediatrics, 2024)
Background: Antiphospholipid syndrome (APS) is an autoimmune disease characterized by recurrent vascular thrombotic events. Catastrophic APS (CAPS), which can result in multiple organ failure and even death, is the most severe manifestation of APS. Herein, we report the case of a pediatric patient with CAPS, including the clinical course, diagnosis, and treatment, with the goal of expanding the literature on this condition, as reports of CAPS in pediatric patients are rare.Case presentation: A 7-year-old girl presented with cranial hypertension. She was initially admitted to the hospital with a diagnosis of cerebral venous sinus thrombosis (CVST) and was discharged following symptom improvement. However, only 3 days later, the patient was represented with cranial hypertension and multiple thromboses and was ultimately diagnosed with CAPS based on multidisciplinary consensus. Despite treatment with a series of anticoagulation and thrombolytic therapies, the child's condition progressed rapidly, and she eventually died of pulmonary embolism.CAPS in children is rare and associated with a high mortality rate, making early recognition and diagnosis critical but difficult. Based on the presented case, we recommend routine screening for antiphospholipid antibodies in children with CVST without obvious triggers, or a multidisciplinary collaboration, to facilitate the early diagnosis of CAPS.